Nutrient Addition and Drought Interact to Change the Structure and Decrease the Functional Diversity of a Mediterranean Grassland - Nogueira, Carla; Nunes, Alice; Bugalho, Miguel N.; Branquinho, Cristina; McCulley, Rebecca L.; Caldeira, Maria Conceição (Frontiers in Ecology and Evolution, 2018)
Anthropogenic activities are increasing nutrient availability and altering precipitation regimes. This may lead to critical changes in grasslands functioning and resilience. This is particularly important for grasslands in the Mediterranean Basin that have evolved in nutrient poor soils, and where more frequent and prolonged droughts are projected to occur. However, there is limited knowledge regarding the interacting effects of multiple nutrient inputs and rainfall variability on Mediterranean grassland functional structure and diversity. We conducted a nutrient addition experiment during four contrasting precipitation years in a Mediterranean grassland. We established four treatments that varied in the number of added nutrients from no added nutrients (control), to one added nutrient (Nitrogen-N, Phosphorus-P or Potassium-K), two added nutrients, (NP, NK or PK) and three added nutrients (NPK). We assessed the effect of increasing nutrient addition in wet, normal, dry and very dry years on species functional traits at the community level. We determined the community functional structure (e.g. Community Weighted Mean, CWM) and functional diversity (e.g. Functional Dispersion, FDis) for eight key functional traits indicators of nutrient and water use strategies. We also assessed if CWM, FDis and species richness were related to the aggregate grassland functioning property, productivity. We found that CWM was affected by nutrient addition and precipitation and, for some traits, by their interaction. However, FDis of most traits was affected by precipitation. The very dry year had a negative effect on FDis of most traits (e.g. dispersal modes, nutrient uptake strategies) and interacted with three added nutrients to decrease FDis of growth-forms. Conversely, FDis of reproductive traits decreased during the wet year. Species richness and FDis were not related to grassland productivity, whereas CWM was the main determinant of grassland productivity supporting the importance of species functional traits in determining ecosystem functioning. Our results highlight drought as a critical factor determining a decrease in the functional diversity of Mediterranean grasslands. Moreover, drought can also interact with nutrient addition changing the dominance of many traits and further decreasing functional diversity. This will have important implications for ecosystem functioning and resilience in the context of global changes.